Alfavitar radi učenija malych detej. Un abbecedario nella Russia del Seicento - BRAGONE, MARIA CRISTINA (Biblioteca di Studi Slavistici, 2008)
The volume presents the edition of a copy of an anonymous Russian manuscript spelling book probably written by the famous scholar Yevfimiy Cudovsky, or by personalities close to him from the Muscovite background of the Philhellenes, in the 1680s. This spelling book represents a significant evidence of the level reached, on the eve of the great reforms introduced by Peter, by the Russian didactic literature intended for elementary education, heir to the tradition established by Ivan Fyodorov with the manual printed in Lviv in 1574. The edition is accompanied by a preface and a commentary that locates the spelling book in the Russian historical-cultural and literary context of the second half of the 17th century, particularly in relation to other books of this kind and grammar manuals circulating at the time.